2009
DOI: 10.1128/jb.00103-09
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Operon in Extraintestinal PathogenicEscherichia coliPromotes Fitness under Stressful Conditions and Invasion of Eukaryotic Cells

Abstract: We identified a carbohydrate metabolic operon (frz) that is highly associated with extraintestinal pathogenic Escherichia coli (ExPEC) strains. The frz operon codes for three subunits of a phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) transporter of the fructose subfamily, for a transcriptional activator of PTSs of the MgA family, for two type II ketose-1,6-bisphosphate aldolases, for a sugar-specific kinase (repressor, open reading frame, kinase family [ROK]), and for a protein of the cupin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 59 publications
3
51
0
Order By: Relevance
“…Horizontal gene transfer probably also explains the presence of PRD-containing regulators in a few spirochaetes (treponemae and brachyspirae). Interestingly, in several pathogenic E. coli strains, genes encoding PRD-containing regulators are sometimes located in pathogenicity islands (55), which also supports the concept of horizontal gene transfer.…”
Section: Proteins Containing a Specific Pts-recognized Phosphorylatiosupporting
confidence: 58%
See 1 more Smart Citation
“…Horizontal gene transfer probably also explains the presence of PRD-containing regulators in a few spirochaetes (treponemae and brachyspirae). Interestingly, in several pathogenic E. coli strains, genes encoding PRD-containing regulators are sometimes located in pathogenicity islands (55), which also supports the concept of horizontal gene transfer.…”
Section: Proteins Containing a Specific Pts-recognized Phosphorylatiosupporting
confidence: 58%
“…There are also numerous proteins of unknown function that contain a PTS domain (6). The PTS-mediated regulation of the lactose transporters from Streptococcus thermophilus (53) and Streptococcus salivarius (54) and of several transcription activators from firmicutes (1) and some Enterobacteriaceae, such as FrzR of E. coli (55), has been studied in detail.…”
Section: Proteins Containing a Pts Component Fused To The N Or C Termmentioning
confidence: 99%
“…It has recently been shown in an APEC strain of serogroup O1 that P fimbriae are involved in the virulence of that strain in chickens (35). Gene frz orf4 is chromosomally located and belongs to the frz operon, which encodes a phosphoenolpyruvate carbohydrate phosphotransferase system transporter and enzymes involved in sugar metabolism (48). A link between the expression of this locus and E. coli pathogenic abilities was confirmed by experiments showing its role in promoting bacterial fitness under stressful conditions, such as oxygen restriction or the late stationary phase of growth, and in promoting growth in chicken serum or the intestinal tract during in vivo competition assays.…”
Section: Discussionmentioning
confidence: 99%
“…Several virulence genes have been demonstrated to be implicated in avian colibacillosis, including those encoding for adhesins (F1, P, and Stg fimbriae, curli, and EA/I), anti-host defense factors (OmpA, Iss, lipopolysaccharide, and K1), iron acquisition systems (aerobactin, Iro proteins, yersiniabactin, and the Sit iron acquisition locus), autotransporters (Tsh, Vat, and AatA), the phosphate transport system, sugar metabolism, and the IbeA protein (1,12,13,24,35,38,48).…”
mentioning
confidence: 99%
“…In this context, we noted that one early study indicated that a PTS system is involved in type-1 fimbriae expression in extraintestinal pathogenic E. coli (ExPEC). 33 We therefore sought to determine whether the NTUH-K2044 kp0760-kp0763 gene cluster (which, as noted above, encodes a PTS system and is positively affected by YfgL) was involved in type-1 fimbriae expression. We compared the fim phase switching of the yfgL mutant with that of the wild-type strain; the yfgL complementation strain; and a pts mutant (kp0760-kp0763) strain.…”
Section: Identification Of the E Coli Recombinant Strains Elevated Imentioning
confidence: 99%